Improvement of crystalline quality of CdZnTe epilayers on GaAs(001) substrates with a two-step growth by Close Spaced Sublimation. (June 2019) - Cao, Kun; Jie, Wanqi; Zha, Gangqiang; Hu, Ruiqi; Wu, Sihong; Wang, Yawei
Abstract: A two-step growth process of CdZnTe(001) epilayers on GaAs(001) substrates by Close Spaced Sublimation (CSS) is proposed. The first step, or a so-called pre-growth at low temperature of 350 °C generates more compact nucleation layer than the second step growth at 430 °C, which is more efficient for accelerating grain coalescence and annihilation of defect. Both the double crystal X-ray rocking curve (DCXRC) and the photoluminescence (PL) results prove that CdZnTe film with the best crystalline quality is obtained with the combination of the first step growth at 350 °C and the second growth at 430 °C. Increasing the second step growth temperature from 430 °C to 530 °C and 600 °C deteriorate films crystalline quality due to the increase in thermal stress and Zn content. Current-voltage (IV) measurement and alpha-particle response test indicate that better crystalline quality in CZT film leads to both higher resistivity and better carrier transport property. Highlights: A two-step growth of CdZnTe(001)/GaAs(001) epilayers by CSS was proposed. The first step growth at 350 °C was more efficient for reducing defects than at 430 °C. The optimum second growth temperature was at 430 °C. Zn contents, residual stress of CZT films were affected by growth temperature. The effect of crystalline quality of CZT film on electrical property has been studied.